2009
DOI: 10.1136/jnnp.2007.136051
|View full text |Cite
|
Sign up to set email alerts
|

A novel NGFB point mutation: a phenotype study of heterozygous patients

Abstract: The NGFB mutation in its heterozygous form results in a milder disease than in homozygotes, with a variable clinical picture, ranging from asymptomatic cases to those with Charcot arthropathy appearing in adult age. Particularly age, but perhaps lifestyle factors also, may influence the development of clinical polyneuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 24 publications
5
39
0
Order By: Relevance
“…So far, only one homozygous missense mutation has been reported, in a recessive Swedish family (Einarsdottir et al ., 2004; Minde et al ., 2004). Detailed clinical, neurophysiological and genetic analysis of this family revealed that the heterozygous carriers presented with a variable but mild phenotype (Minde et al ., 2009). The main difference with CIPA was the absence of obvious mental retardation and less-pronounced anhidrosis.…”
Section: Discussionmentioning
confidence: 99%
“…So far, only one homozygous missense mutation has been reported, in a recessive Swedish family (Einarsdottir et al ., 2004; Minde et al ., 2004). Detailed clinical, neurophysiological and genetic analysis of this family revealed that the heterozygous carriers presented with a variable but mild phenotype (Minde et al ., 2009). The main difference with CIPA was the absence of obvious mental retardation and less-pronounced anhidrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although not suffering from painless fractures, they can manifest Charcot arthropathies at single or multiple joints, particularly in the lower extremities. Cognitive functions and basic reflexes are normal in carriers (Einarsdottir et al 2004;Minde et al 2004Minde et al , 2006Minde et al , 2009. A list of the most relevant clinical features of R221W carriers is provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…This noninvasive method has been applied to quantify C-fiber loss in neuropathy secondary to diabetes and other etiologies (Einarsdottir et al 2004;Minde et al 2004Minde et al , 2006Minde et al , 2009Quattrini et al 2007;Tavakoli et al 2009Tavakoli et al , 2010Tavakoli et al , 2012. To further investigate the contribution of C-fiber density to clinical pain assessment scores and subjective pain evaluation, we also administered the Neuropathy Disability Score (NDS; Young et al 1993) and the Situational Pain Questionnaire (SPQ; Clark and Yang 1983).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date only one NGFB point mutation has been described in a family with HSAN V (p.Arg221Trp) [4, 16], one family with HSAN IV was reported with a homozygous frameshift mutation due to a point mutation and two base pair deletion on the same allele (p.Val232fs) [1] and one patient with a sensory and autonomic neuropathy has been described with heterozygous deletion of 12 genes one of which was NGFB [5]. Although HSAN V is usually recessive, there is a suggestion that heterozygotes have a higher incidence of Charcot joints and neuropathy, as reported in a large family with p.Arg221Trp [15]. Our patient with a heterozygous duplication (p.Gly161_Glu162dup) has a similar phenotype; however, it is currently not possible to confirm whether this variant is pathogenic.…”
Section: Discussionmentioning
confidence: 99%